Proactive university students’ views on skills gained from a research colloquium - Nolasco-Salcedo, Ma del Carmen; Alfaro-Castellanos, Kleophe; Carranza-Sahagun, Diego Ulises; Ávila-Paz, José; Ávila-Paz, Angelica Patricia (Institute of Advanced Engineering and Science, 2025)
Research is a key component of higher education, promoting deep learning, critical thinking, and problem-solving skills. The Academic Body of Engineering and Systems (InySis) organizes the colloquium of research initiation: proactive university students (CIIEUPA) each academic cycle (A and B) to foster research as a fundamental tool for students’ educational and professional development. This qualitative, descriptive study aimed to determine the skills acquired by students participating in CIIEUPA. The action-research methodology was employed, with participant observation used as the data collection technique. The sample consisted of second and third-semester students from the Software Engineering Competence Unit from the 2022A and 2022B cycles. The results revealed that participation in the colloquium enriched students with experiences that fostered teamwork, effective communication, critical thinking, and leadership. CIIEUPA, as an active collaborative learning methodology, allowed students to share their findings with the academic community, strengthening their commitment, and motivation toward research. Such initiatives contribute to learning and play a crucial role in the holistic development of students, promoting their growth in both academic and professional fields. This approach demonstrates the value of integrating research into the educational process, allowing students to engage meaningfully with their discipline while developing essential skills for their future careers.